Cecal volvulus - Revoredo Rego, Fernando (2021)
Cecal volvulus involves the proximal right colon, the cecum and the terminal ileum. Two requirements are needed, an incomplete fixation of the cecum and the restriction of the bowel movement at a fixed point which serves as a fulcrum for rotation. We present a case of a 52-year-old woman who was admitted with the diagnosis of an acute intestinal obstruction. The preoperative diagnosis was made with a tomography and she underwent a laparoscopic assisted right colectomy with primary anastomosis. In these patients, the right colon nononcologic surgical resection is recommended because eliminates the possibility of volvulus recurrence. Colonoscopy, cecopexy, or cecostomy should be avoided because its associated significant recurrence, morbidity and mortality.